Rapid screening for SARS-CoV-2 VOC-Alpha (202012/01, B.1.1.7) using the Allplex™ SARS-CoV-2/FluA/FluB/RSV Assay. (December 2021) - Giovacchini, Nicla; Coppi, Marco; Aiezza, Noemi; Baccani, Ilaria; Malentacchi, Francesca; Pollini, Simona; Antonelli, Alberto; Rossolini, Gian Maria
HIGHLIGHTS: Rapid detection of SARS-CoV-2 variants of concern (VOCs) might be of epidemiological importance Cq difference between N and S genes was found only with VOC-Alpha using the ASFR assay This peculiar positivity profile could be a useful proxy for tracking VOC-Alpha ABSTRACT: Background: The emergence of SARS-CoV-2 variants of concern (VOCs) for increased transmissibility and being potentially capable of immune-escape mandates for epidemiological surveillance. Genomic alterations present in VOCs can affect the results of RT-qPCR assays for routine diagnostic purposes, leading to peculiar profiles that can be used for rapid screening of variants. This study reports a peculiar profile observed with the Allplex™ SARS-CoV-2/FluA/FluB/RSV assay and VOC-Alpha (202012/01, lineage B.1.1.7, also named VOC-UK), which was the first identified SARS-CoV-2 VOC. Methods: Samples were analyzed by two RT-qPCR assays: the Allplex™ SARS-CoV-2/FluA/FluB/RSV assay (ASFR, Seegene Technologies Inc; Seoul, South Korea) and the TaqPath COVID-19 RT-PCR (Thermo Fisher Scientific, USA). Definition of the SARS-CoV-2 variant was carried out by Sanger sequencing of the relevant S-gene regions and, in some cases, by whole genome sequencing (WGS) using the ARTIC-nCoV workflow on a MiniION (Oxford Nanopore Technologies, Oxford, UK) or a Illumina MiSeq platform (San Diego, California, USA). Results: Of the 173 SARS-CoV-2-positive specimens, all those of lineage B.1.1.7 (N=71) showed an average Cq difference between the N and S genes of +11±2 (range, +8/+15). None of the other specimens, including several different lineages (Wild-type for the analyzed regions, N=22; Gamma, N=63; Delta, N=9; B.1.258Δ, N=3; B.1.160, N=3; B.1.177.7, N=1; B.1.1.420, N=1), exhibited a similar difference in Cq values. Conclusions: The peculiar pattern of delayed N gene positivity could constitute a convenient method for VOC-Alpha screening, simultaneous to viral detection, when using the Allplex™ SARS-CoV-2/FluA/FluB/RSV assay.